Over a million students use our free study notes to help them with their homework
(a) To differentiate implicitly, differentiate x’s as normal and differentiate y’s with respect to y before multiplying by dy/dx. Therefore the differentiating the curve gives9x^(1/2) + 10y*(dy/dx) ...
Differentiate to get:dy/dx = 12x^3 -24x^2Factorise and set equal to 0:12x^2(x-2) = 0Solve to get x = 2 and x =0.
Integrate by parts once to obtain: xe^x - e^x + c
First we notice that y can be written as the product of two functions of x, u = x and v = (3x + 5)^3. This means we can use the product rule to differentiate which is dy/dx = uv' + vu'. We can plug our fu...
dy/dx = 2x -2 -12x^(-1/2)
←
138
139
140
141
142
→
Internet Safety
Payment Security
Cyber
Essentials